Supine and Standing AP Pelvis Radiographs in the Evaluation of Pincer Femoroacetabular Impingement. Issue 7 (July 2016) - Jackson, Timothy J.; Estess, Allyson A.; Adamson, Gregory J.
Abstract: Background: Pelvic tilt can affect the presence of the ischial spine sign and crossover sign. Numerous studies of pelvic tilt on radiographic measurements of pincer impingement have shown that increasing anterior tilt is associated with more radiographic signs of pincer impingement. However, to our knowledge, no study has directly compared supine and standing plain radiographs in patients with respect to lateral center‐edge (LCE) angle, acetabular inclination, crossover sign, and ischial spine sign. Questions/purposes: The purpose of this study was to evaluate the differences in supine and standing AP pelvis radiographs as they relate to the radiographic parameters of pincer impingement in an adult population evaluated for femoroacetabular impingement, specifically intrapelvic distances (sacrococcygeal to symphysis [SC‐S] and coccyx tip to symphysis [T‐S]), crossover sign (presence and percentage), LCE angle, inclination, and ischial spine sign. Methods: Between August 2013 and June 2014, we obtained supine and standing radiographs for all new patients younger than 60 years who were evaluated for hip pain, when the diagnosis of fracture was not being considered; these formed the basis of this retrospective study. Patients were excluded if they had arthritis (Tönnis grade ≥ 2), lumbar fusion, previous hip surgery, or malrotated films. Forty‐six hips, symptomatic side, met the inclusion criteria (age of patients, 33 ± 14 years; 13 males, 33 females). Radiographic data that were collected included SC‐S distance, T‐S distance, LCE angle, acetabular inclination, presence and percentage of crossover sign, and presence of ischial spine sign. A paired t‐test was used to compare continuous variables and chi‐square test was used for categorical variables. Two independent readers performed measurements. Results: From supine to standing films, the T‐S distance decreased from 19 ± 18 mm to 6 ± 19 mm (p < 0.001), and SC‐S distance decreased from 47 ± 19 mm to 32 ± 20 mm (p < 0.001), indicating less pelvic tilt in the standing position. The number of hips that had crossover signs decreased from supine (n = 18, 39%) to standing (n = 9, 20%) (p = 0.039). The amount of crossover decreased from 23% ± 10% to 11% ±13% (p < 0.001). LCE angle did not change (27° ± 7° to 27° ± 8°) (p = 0.64) and inclination angle increased by a small amount (4.2° ± 5° to 5.3° ± 5°) (p = 0.002). The ischial spine sign decreased from supine (n = 20, 43%) to standing (n = 7, 15%) position (p = 0.003). Conclusions: There is a decrease in the amount of pelvic tilt on standing AP pelvis radiographs resulting in a decrease in the incidence and amount of crossover sign and ischial spine sign, and a small increase in inclination. Standing radiographs should be the standard in evaluation of nonarthritic hip pain, specifically pincer femoroacetabular impingement. Surgeons should use caution in interpreting supine AP radiographs in the evaluation of pincer impingement, specifically the crossover sign. Level of Evidence: Level III, diagnostic study.